Near‐Bed Sediment Transport Processes During Onshore Bar Migration in Large‐Scale Experiments: Comparison With Offshore Bar Migration. Issue 3 (18th March 2023) - Grossmann, Florian; Hurther, David; van der Zanden, Joep; Sánchez‐Arcilla, Agustín; Alsina, José M.
Abstract: Detailed information on nearshore sediment transport processes during onshore bar migration were obtained from large‐scale laboratory experiments with bichromatic wave groups on a relatively steep initial beach slope (1:15). Detailed measurements of velocity and sand concentration near the bed from shoaling up to the outer breaking zone including suspended sediment and sheet flow transport are presented. The analysis focuses on onshore migration under an accretive wave condition but comparison to an erosive condition highlights important differences. Decomposition shows that total transport mainly results from a balance of short wave‐related, bedload onshore transport and current‐related, suspended offshore transport. When comparing the accretive to the more energetic erosive condition, the balance shifts toward onshore transport, and onshore migration, because the short wave‐related transport does not decrease as much as the current‐related transport. This is related to the effects of skewness and asymmetry combined with less sediment suspension in the water column and undertow magnitude under the accretive condition. Transports from streaming in the wave boundary layer and from infragravity waves become visible but only play a subordinate role. Identified priorities for numerical model development include parametrization of wave nonlinearity effects and better description of wave breaking and its influences on sediment suspension. Plain Language Summary: Nearshore sandbars are seabed features that protect coastal infrastructure behind many sandy beaches around the world. In response to waves they change in shape and distance to the beach. To improve understanding of their onshore and offshore movement (migration), experiments representing natural conditions in a controlled laboratory setting were done. In this context, the underwater transport of sand was measured on the basis of flow velocities and sediment concentration in the water. The most important factors for migration direction were: shape of the waves (asymmetries about horizontal and vertical axes), wave breaking and resulting flows, and processes to lift sediments into the water column and keep them suspended. Under storm waves, the breaking‐induced flows dominated the sediment transport so that bars moved offshore. In calmer conditions, the shape of the waves dominated the transport so that bars moved onshore. The inherent complexities of these processes make their mathematical replication difficult, as shown by comparison to literature. Consequently, priorities for advancing the forecasting of sandbar movement, improving coastal protection, were identified. Key Points: Migration results from balance of onshore‐directed, short‐wave related bedload and offshore‐directed, current‐related suspended transports From storm to recovery waves there is change to onshore migration because stronger reduction in offshore‐ than onshore‐directed transports Streaming and infragravity wave influences are visible but negligibly low; wave breaking and nonlinearity influences are more important